The teacher's authority in the view of Professor Maria Dudzikowa - a poem written - Justyna Miko-Giedyk (Studia z Teorii Wychowania)
The text is a literary work based on the consideration of Professor Maria Dudzikowa around the teacher's authority. It is an appeal to teachers to become reflective practitioners.